The methods and principles of teaching foreign language (Eurasian Journal of Learning and Academic Teaching, 2022)
Today the professional language teacher has a good grounding in the various techniques and new approaches, and they know and understand the history and evolution of teaching methodologies. The modern teacher will in fact use a variety of methodologies and approaches, choosing techniques from each method that they consider effective and applying them according to the learning context and objectives.